THE MAIN THEMES IN J.F. COOPER’S NOVEL “THE LAST OF THE MOHICANS” - Tukhtaeva Nargiskhan Isomiddinovna; Narzullaeva Dildora Obitovna; Bakhshillaeva Nafosat Anvarovna (Galaxy International Interdisciplinary Research Journal, 2022)
Cooper’s The Last of the Mohicans is seen as not only romantistic, but as actively anti sentimental. In nineteenth – century sentimental theory, sight was one of the primary conduits to the emotions. When one beheld the sight of suffering, the theory went; one could not help but develop pity for the object of that suffering. Cooper wrote the novel as an explicit rejection of sentimental positions staked out by Lydia Maria Child in Hobomok: “He is resisting or rejecting the fantasy of women’s novels that women’s elevated place in white society is a function of a spiritual power by which male physical force can be countered, contained, and even disarmed denies that women have influenced world or national events and uses the romanticizing of American Indians in women’s novels as evidence of their unfitness for the cultural power to which they were apparently aspiring”.